CARDIAC LESION IN CHURG - STRAUSS SYNDROME - E. S. Eniseeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Cardiac involvement is the most important prognostic factor in eosinophilic granulomatosis with polyangiitis (Churg - Strauss syndrome). We report a case of Churg - Strauss syndrome in 65-year-old women masquerading as a non-ST elevation myocardial infarction. She had chest discomfort, dyspnea and ST depression, high troponin level and so myocardial infarction was diagnosed. She had had asthma for 4 years but had no eosinophilia in peripheral blood and lesions in the lungs at the time of the first hospitalization. Her skin was clean without rashes. 3 months later she was hospitalized again having pulmonary infiltrates. Laboratory tests revealed that eosinophil was significantly increased. Cardiac involvement in a pathological process led to death. Histological examination of heart and lungs showed necrotic coronary vasculitis, granulomas and perivascular eosinophilic infiltrates in myocardium, endocardium, pericardium and pulmonary eosinophilic infiltrates.